Pengembangan Media Pembelajaran Interaktif Articulate Storyline Berbasis Keterampilan Berpikir Kritis pada Pembelajaran IPA bagi Siswa Sekolah Dasar - Legina, Nadia; Sari, Prima Mutia (Jurnal Paedagogy, 2022)
This study aims to create a new product in the form of Articulate Storyline interactive learning media based on elementary school students’ critical thinking skills in science learning. The study used Research & Development (R&D) and the ADDIE model, which had five stages: analysis, design, development, implementation, and evaluation. The data analysis technique in this study used qualitative & quantitative techniques. Qualitative data were obtained through interviews, comments, and suggestionsâ€”meanwhile, quantitative data were obtained through questionnaires to validators, educators, and students. The validation test results given by material experts had an average of 91% of the categories obtained as very feasible, and the validation test results given by media experts also had an average of 91%, including the very feasible category. The assessment results of educators’ responses to the media obtained an average percentage of 93%, with an excellent category. The response of students’ assessments to the media obtains an average percentage of 89% and found the category was outstanding. The data above proves that Articulate Storyline interactive learning media based on critical thinking skills in class V science learning for Elementary School students is suitable for the science learning process.